2014
DOI: 10.1037/a0034828
|View full text |Cite
|
Sign up to set email alerts
|

The creative person in science.

Abstract: The psychological qualities of the creative person in general are gradually becoming more and more clear, and yet the psychological qualities of the creative scientists remain less clear. The current investigation examined the personality characteristics of the creative scientist in a sample of 145 academic physical, biological, and social scientists (33% women) from major research universities throughout the United States. Personality data were collected online through completion of the Big Five Inventory (Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 98 publications
1
52
0
9
Order By: Relevance
“…Moreover, prior research found that the intellectual dimensions of openness related to being a scientist (Barton, Modgil, & Cattell, 1973) and to scientific creative accomplishments (Kaufman, 2013). 1 Also, a recent study found that openness was the strongest personality correlate of scientific creativity, as measured via journal publications (b D .21; Grosul & Feist, 2014). Given the connection between openness and science, it seems clear that openness is related to performance in a scientific environment.…”
Section: Learning Approach and Performancementioning
confidence: 94%
“…Moreover, prior research found that the intellectual dimensions of openness related to being a scientist (Barton, Modgil, & Cattell, 1973) and to scientific creative accomplishments (Kaufman, 2013). 1 Also, a recent study found that openness was the strongest personality correlate of scientific creativity, as measured via journal publications (b D .21; Grosul & Feist, 2014). Given the connection between openness and science, it seems clear that openness is related to performance in a scientific environment.…”
Section: Learning Approach and Performancementioning
confidence: 94%
“…In peer-reviewed studies with adequate sample sizes, openness and OE have high correlations with creativity Feist, 1998;Furnham et al, 2011;Furnham et al, 2013;Gorman & Feist, 2014;Hughes et al, 2013;Ivcevic & Mayer, 2007;Kerr & McKay, 2013;Wolfradt & Pretz, 2001;YakmaciGuzel & Akarsu, 2006) and moderate correlations with intelligence in samples of all ability levels Cross et al, 2007;Gignac et al, 2004;Harris, 2004;Moutafi et al, 2003;Moutafi et al, 2006;Sak, 2004;Zeidner & Shani-Zinovich, 2011). Brain imaging studies show that openness and OEs seem to be largely represented in the same brain area, BA 40 DeYoung, 2010;DeYoung et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Openness to experience and intellectual curiosity were among the traits that discriminated between creative and noncreative people (Ivcevic & Mayer, 2007). In a study of scientific creativity, openness was the only significant predictor among other personality factors based on the five-factor model and Eysenck's three factors; openness predicted number of citations received by a scientist, their hindex, their Soler creativity index (which takes into account citations of a paper, references cited in that paper, number of authors per paper, and total publications by one author), and an overall score including the aforementioned criteria plus number of lifetime publications (Gorman & Feist, 2014).…”
Section: Openness To Experience and The Five-factor Model Of Personalitymentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, research on how researchers interact with and use digital publishing at the individual level is somewhat limited.…”
Section: July 2018mentioning
confidence: 99%